Organic Computing : Doctoral Dissertation Colloquium 2015 - Sven Tomforde; Bernhard Sick (Kassel University Press GmbH_Legacy, 2015)
This book consists of fourteen different contributions that can be grouped into five major categories reflecting the different aspects of current OC research in general: (1) trustworthiness, (2) swarm behaviour, (3) security and testing, (4) self-learning, and (5) hardware aspects.